Factors Used to Determine the Teaching Load for Chairs in Public Community Colleges - Mandel Samuels; James O. Hammons (Academic Chairpersons Conference Proceedings, 2018)
After a 10 minute presentation of a recently completed national study of the practices used by public community colleges to determine chair teaching load, attendees will be provided a framework and procedure for determining chair teaching load on their campus, and will then engage in a spirited but structured discussion of the factors to be considered and a process for assigning weights to each.
Keywords: community college; chairperson; workload; factors; weights